Antiretroviral therapy in pregnant women living with HIV: a clinical practice guideline - Siemieniuk, Reed A C (BMJ, 2017)
Approximately 1.4 million women living with HIV become pregnant every year. Most women use antiretroviral therapy, to reduce the risk of vertical transmission or for personal health reasons. Using the GRADE framework according to the BMJ Rapid Recommendation process, we make recommendations for optimal choice of combination antiretroviral regimen considering patient values and preferences, the balance of desirable and undesirable outcomes, their uncertainty, and practical issues. We suggest a zidovudine and lamivudine-based regimen over one that includes tenofovir or emtricitabine (weak recommendation). We recommend alternatives over the combination of tenofovir, emtricitabine, and lopinavir/ritonavir (strong recommendation).